UV-Technologies for Disinfection of Water, Air and Surfaces: Principles and Possibilities - S. V. Kostuchenko; A. A. Tkachev; T. N. Frolikova (Эпидемиология и вакцинопрофилактика)
Relevance. For over 30 years, ultraviolet bactericidal radiation has been widely used to disinfect water, air and surfaces. Currently, UV technologies are being dynamically introduced into various spheres of the national economy – industry, medicine, utilities, energy, transport, agriculture, etc.Aims of this message to present the possibilities of UV radiation for the disinfection of water, air, and surfaces.Conclusions. The task of disinfecting natural and waste waters was the driver of the development of UV technologies in the last 30 years. The scale of this task forced the world's leading institutions and lighting companies to raise the development and production of UV radiation sources (UV lamps) to a new level. In recent years, is in the usage of UV radiation for disinfection of air and air conditioning systems of buildings as a whole. Global migrations and communications of the population around the planet have aggravated the situation with the spread of infectious diseases transmitted by airborne droplets. In last decades, epidemics have ceased to be a local territorial phenomenon. A prime example is the current global COVID-19 pandemic caused by the SARS-CoV-2 coronavirus. In medicine, the highest requirements are imposed on the disinfection of air and surfaces with a high degree of disinfection. To solve this problem, it is necessary to pay special attention to modern developments in the application of UV technologies, taking into account the effective UV doses in relation to various types of microorganisms.